2018
DOI: 10.7759/cureus.2299
|View full text |Cite
|
Sign up to set email alerts
|

Bouveret's Syndrome: Literature Review

Abstract: It was in 1896 that Bouveret’s syndrome acquired its name after the French physician Leon Bouveret, who published two case reports in Revue de Medecin. Bouveret’s syndrome describes gastric outlet obstruction secondary to an impacted gallstone. The gallstone reaches the small bowel through a bilioenteric fistula as a consequence of chronic inflammation and adherence between the biliary system and the bowels which increase the intraluminal pressure and leads to secondary wall ischemia and wall perforation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(116 citation statements)
references
References 5 publications
1
102
0
13
Order By: Relevance
“…One of the complications of the cholecystoduodenal fistula was presented in our second case -Bouveret syndrome, which implies proximal duodenal or distal stomach obstruction by biliary calculus. It is a rare syndrome that affects elderly women with previous history of biliary calculosis [6,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the complications of the cholecystoduodenal fistula was presented in our second case -Bouveret syndrome, which implies proximal duodenal or distal stomach obstruction by biliary calculus. It is a rare syndrome that affects elderly women with previous history of biliary calculosis [6,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…A review of 1,001 cases concluded that simple enterolithotomy was both safe and effective in managing patients with gallstone ileus [23]. It is still a matter of debate whether cholecystectomy and repair of the fistula should be performed, due to spontaneous closure of fistulas in some cases [6,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the surgical approach used, examining the remaining small intestine is paramount for excluding the presence of any intestinal gallstones that could result in a future obstruction. 8 Cholecystectomy and fistula repair are recommended to reduce the risk of future recurrence, gallstone pancreatitis, gallstone ileus, and gallbladder cancer, 4 and they can be performed in one or two stages. Fistula repair options include primary closure, an omental patch, jejunoduodenostomy, and in rare instances, a Whipple pancreaticoduodenectomy.…”
Section: Various Surgical Techniques Of Stone Extraction Have Beenmentioning
confidence: 99%
“…2,7 Moreover, 42% of patients who required surgery had failed at least one endoscopic trial for removing the stones. 2,8 Nevertheless, surgical treatment carries an increased risk of morbidity and mortality. 1 Surgery should be considered in hemodynamically unstable patients, patients who fail endoscopic treatment trials, and those with concurrent distal gallstone ileus.…”
mentioning
confidence: 99%